Brain Aβ load association and sexual dimorphism of plasma BACE1 concentrations in cognitively normal individuals at risk for AD. Issue 10 (1st October 2019) - Vergallo, Andrea; Houot, Marion; Cavedo, Enrica; Lemercier, Pablo; Vanmechelen, Eugeen; De Vos, Ann; Habert, Marie‐Odile; Potier, Marie‐Claude; Dubois, Bruno; Lista, Simone; Hampel, Harald; ,; et al.
Abstract: Introduction: Successful development of effective β‐site amyloid precursor protein cleaving enzyme 1 (BACE1)–targeted therapies for early stages of Alzheimer's disease requires biomarker‐guided intervention strategies. Methods: We investigated whether key biological factors such as sex, apolipoprotein E ( APOE ε4 ) allele, and age affect longitudinal plasma BACE1 concentrations in a large monocenter cohort of individuals at risk for Alzheimer's disease. We explored the relationship between plasma BACE1 concentrations and levels of brain amyloid‐β (Aβ) deposition, using positron emission tomography global standard uptake value ratios. Results: Baseline and longitudinal mean concentrations of plasma BACE1 were significantly higher in women than men. We also found a positive significant impact of plasma BACE1 on baseline Aβ–positron emission tomography global standard uptake value ratios. Discussion: Our results suggest a sexual dimorphism in BACE1‐related upstream mechanisms of brain Aβ production and deposition. We argue that plasma BACE1 should be considered in further biomarker validation and qualification studies as well as in BACE1 clinical trials.